Perinatal mortality and its predictors in Kersa Health and Demographic Surveillance System, Eastern Ethiopia: population-based prospective study from 2015 to 2020 - Yadeta Dessie; Merga Dheresa; Gamachis Daraje; Gelana Fekadu; Galana Mamo Ayana; Bikila Balis; Belay Negash; Temam Beshir Raru; Addisu Alemu; Bedasa Taye Merga (BMJ Open)
Objective Perinatal mortality is an important outcome indicator for newborn care and directly mirrors the quality of prenatal, intra partum and newborn care. Therefore, this study was aimed at estimating perinatal mortality and its predictors in Eastern Ethiopia using data from Kersa Health and Demographic Surveillance System (KHDSS).Design, settings and participants An open dynamic cohort design was employed among pregnant women from 2015 to 2020 at KHDSS. A total of 19 687 women were observed over the period of 6 years, and 29 719 birth outcomes were registered.Outcome measures Perinatal mortality rate was estimated for each year of cohort and the cumulative of 6 years. Predictors of perinatal mortality are identified.Results From a total of 29 306 births 783 (26.72 deaths per 1000 births; 95% CI 24.88 to 28.66) deaths were occurred during perinatal period. Rural residence (adjusted OR (AOR)=3.43; 95% CI 2.04 to 5.76), birth weight (low birth weight, AOR=3.98; 95% CI 3.04 to 5.20; big birth weight, AOR=2.51; 95% CI 1.76 to 3.57), not having antenatal care (ANC) (AOR=1.67; 95% CI 1.29 to 2.17) were associated with higher odds of perinatal mortality whereas the parity (multipara, AOR=0.46; 95% CI 0.34 to 0.62; grand multipara, AOR=0.31; 95% CI 0.21 to 0.47) was associated with lower odds of perinatal mortality.Conclusions The study revealed relatively high perinatal mortality rate. Place of residence, ANC, parity and birth weight were identified as predictors of perinatal mortality. Devising strategies that enhance access to and utilisations of ANC services with due emphasis for rural residents, primipara mothers and newborn with low and big birth weights may be crucial for reducing perinatal mortality.